Evaluation on frictional performance of three different oil-lubricated impregnated graphite seal rings for aircraft integrated drive generators - Huiying Qi; Xiao Wang; Rui Zhang; Zhangheng Chen; Shaokan Zheng; Tao Jiang; Jimin Xu (Materials Research Express, 2023)
The frictional performance of the shaft-end graphite seal rings plays a critical role in determining the maintenance-free duration of aircraft integrated drive generators, and significantly depends on the types of graphite materials used. In this study, three types of graphite materials, including epoxy resin, metal antimony and furan resin impregnated ones, were selected for evaluation using a rotating-type tribometer. The frictional test configuration involved an actual graphite seal ring sliding against the surface of a 12Cr2Ni4A disc under the lubrication of 4050 high-temperature synthetic aerospace lubricating oil, which was highly consistent with the practical operational conditions. The frictional performance of the three different impregnated graphite seal rings, including coefficient of friction, two-dimensional (2D)/three-dimensional (3D) morphologies of wear marks and wear rate of ring mass, were quantitatively analyzed and compared. The experimental results indicated that the metal antimony-impregnated graphite seal ring behaved with the smallest coefficient of friction among the three seal rings. 2D and 3D surface roughness parameters of the metal antimony impregnated graphite seal are the smallest. The wear rate of the seal ring’s mass is only approximately 22% of that of furan resin impregnated seal ring. The corresponding investigations demonstrated that the currently employed epoxy resin-impregnated graphite seal rings could be replaced by new candidates with better frictional performance to improve the service life.